The Contribution Analysis of Online and Offline Travel Agent in Increasing Room Occupancy - Suwijati, Ni Made (Bali Membangun Bali: Jurnal Bappeda Litbang, 2019)
The research enlightens the contribution of online and offline travel agent in increasing room occupancy at a 5-star hotel located in the southern part of Bali, and determining the most suitable strategy dealing with agent based on the Boston Consulting Group (BCG) matrix. This research aimed at analyzing the contribution of online and offline travel agent in increasing the room occupancy. Data collection techniques used were observations, interviews, documentation and literature studies. The analysis techniques used were descriptive statistics of mean, frequinsing supported by qualitative analysis: (BCG). The results of the research reveal that the contribution of online and offline travel agent for three years has fluctuated. The average contribution of online travel agent in 2016-2018 is 37.73%, while the average contribution of offline travel agent reservation of the period is 52.02%. There are 5 highest reservation contributions sourced from the offline travel agent which included Corona, Maestro, Go Vacation, Jason Travel, and Windys. In addition, there are 5 highest reservation contributions sourced from online travel agents which included Booking.com, Expedia, Agoda, Hotelbeds FIT, and Ctrip.com. Based on BCG matrix to determine the relative market share, it is concluded that the relative market share of the hotel in 2018 is 1.02 times > 1 which means that the hotel has the highest market share among the hotel used as comparison in this reserach. In addition, based on the position of the hotelin BCG matrix in 2018 is at star position which indicates that the hotel’s position is on high growth and high market share, it is because the market share of the hotel has a relative market share value over than one (>1).